Dementia Home Care Resources: How Are We Managing?. (29th October 2011) - Ward-Griffin, Catherine; Hall, Jodi; DeForge, Ryan; St-Amant, Oona; McWilliam, Carol; Oudshoorn, Abram; Forbes, Dorothy; Klosek, Marita
Abstract : With the number of people living with dementia expected to more than double within the next 25 years, the demand for dementia home care services will increase. In this critical ethnographic study, we drew upon interview and participant data with persons with dementia, family caregivers, in-home providers, and case managers in nine dementia care networks to examine the management of dementia home care resources. Three interrelated, dialectical themes were identified: (1) finite formal care-inexhaustible familial care, (2) accessible resources rhetoric-Iinaccessible resources reality, and (3) diminishing care resources-increasing care needs . The development of policies and practices that provide available, accessible, and appropriate resources, ensuring equitable, not necessarily equal, distribution of dementia care resources is required if we are to meet the goal of aging in place now and in the future.